Impact of employment and income support interventions on the health of young adults with episodic disability: Findings from a systematic review - Arif Jetha; Lahmea Navaratnerajah; Sebastian Kondratowski; Meagan Parmassar; Lori B Tucker; Monique AM Gignac (Scandinavian Journal of Work, Environment & Health, 2024)

(untitled)
OBJECTIVE: Young adults living with episodic disabilities face unpredictable disruptions to their employment and health. Our study aimed to examine the impact of employment and income support interventions on the health and well-being of young adults living with episodic disabilities. METHODS: We conducted a systematic review of peer-reviewed intervention studies published in 2001–2021 in industrialized contexts. Two independent reviewers screened titles, abstracts and full-texts. We undertook a narrative synthesis of eligible articles. RESULTS: Our search yielded 15 269 published articles, of which only five studies were eligible for evidence synthesis. All articles were appraised as being of medium quality. Four interventions focused on young adults living with mental health conditions. Two were based in clinical settings; three were based in community-based settings. Each employment intervention exhibited improvements in health outcomes. Three studies examined the impact of supported employment interventions that were particularly beneficial to improving work and health outcomes. CONCLUSION: Involvement in employment interventions could provide benefits for the health of young adults living with episodic disabilities. Our systematic review highlights the need for research to elaborate on the ways in which employment interventions can impact the health and well-being of young adults living with different episodic disabilities.